2023
DOI: 10.1519/jsc.0000000000004608
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Post Practice Changes in Countermovement Vertical Jump Force-Time Metrics in Professional Male Basketball Players

Dimitrije Cabarkapa,
Damjana V. Cabarkapa,
Nicolas M. Philipp
et al.

Abstract: Cabarkapa, D, Cabarkapa, DV, Philipp, NM, Knezevic, OM, Mirkov, DM, and Fry, AC. Pre-post practice changes in countermovement vertical jump force-time metrics in professional male basketball players. J Strength Cond Res 37(11): e609–e612, 2023—Despite the countermovement vertical jump (CVJ) being one of the most popular noninvasive and time-efficient methods for monitoring neuromuscular status, there is a lack of scientific literature focused on examining fatigue-induced alterations in performance in elite ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The selection of the dependent variables included in this investigation was based on previously published research reports that demonstrated adequate levels of validity and reliability ( 23 25 , 31 33 ). The force-time metrics examined within the eccentric phase of the CVJ were: braking phase duration and impulse, eccentric duration, peak velocity, and mean and peak force and power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the dependent variables included in this investigation was based on previously published research reports that demonstrated adequate levels of validity and reliability ( 23 25 , 31 33 ). The force-time metrics examined within the eccentric phase of the CVJ were: braking phase duration and impulse, eccentric duration, peak velocity, and mean and peak force and power.…”
Section: Methodsmentioning
confidence: 99%
“…With rapid technological growth over the last decade, the countermovement vertical jump (CVJ) performed on portable force plate systems has become a gold-standard testing modality in an applied sports setting for the assessment of lower-body neuromuscular performance characteristics ( 23 26 ). It allows sports practitioners to obtain in-depth insight into multiple force-time metrics during both eccentric and concentric phases of the jumping motion with high levels of validity and reliability ( 25 27 ). Yet, despite jumping performance being one of the key physical performance attributes that handball players need to possess to proficiently perform sport-specific movements such as throwing and blocking ( 3 ), previous studies found no differences in jump height when examining elite and amateur male and female handball players ( 13 , 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the on-court competitive demands, basketball players are required to possess adequate levels of lower-body strength and power, regardless of the playing position (4)(5)(6)(7)(8)(9). Alongside tactical-technical comprehension and proficiency, these physical performance parameters are known to be of critical importance for successful participation in the game of basketball (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…When performed on portable force plate systems that allow rapid data analysis, a plethora of force-time metrics can be obtained with high levels of validity and reliability ( 16 , 20 ). This includes metrics within both the eccentric and concentric phases of the jumping movement, which offers a comprehensive movement analysis and avoids quantifying an athlete's performance based on a single variable (e.g., jump height) ( 12 , 18 , 19 ). For example, a series of recently published research reports examined changes in CVJ force-time metrics pre-post practice, differences between playing positions (e.g., guards, forwards, centers), and differences between starters and non-starters at the professional level of men's basketball competition ( 6 , 12 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation